Comparison of astigmatism following manual small incision cataract surgery: superior versus temporal approach - Malik, VK; Kumar, S; Kamboj, R; Jain, C; Jain, K; Kumar, S (Nepalese Journal of Ophthalmology, 2012)
Introduction: Now-a-days, all techniques of cataract extraction are meant for giving the best uncorrected visual acuity and early post-operative rehabilitation. Purpose: To compare astigmatism induced by the superior and temporal section in manual small incision cataract surgery (SICS) in the Indian population. Materials and methods: One hundred and ten eyes were taken. Eyes having a steeper vertical keratometry reading were assigned to the superior SICS group whereas eyes with a steeper horizontal keratometry reading were assigned to the temporal SICS group. Eyes with no astigmatism were randomly assigned to either of the two groups. Both the groups had 54 eyes each. Eyes in Group 1 underwent manual SICS with a superior tunnel and eyes in Group 2 underwent manual SICS with a temporal tunnel. The patients were examined on postoperative Day1, 1 week, 45 days, and 3 months. Uncorrected and best-corrected visual acuity was recorded, slit-lamp examination, auto-refracto-meter and keratometry examinations were done. Statistics: All calculations were performed using surgically-induced astigmatism (SIA) Calculator version 1.0, a free software program. Results: In Group 2, only 35 eyes out of 54 completed the follow-up of 90 days. The mean SIA in Group1 was found to be 1.45 ± 0.7387 and in Group 2 it was 0.75± 0.4067. The z score applied was found to be 5.7143. This value was more than the standard value, i.e.2.58. The p value accordingly was < 0.001, which is highly significant. The SIA induced by the superior incision was 48.28 % more than by the temporal incision. Conclusion: SICS with the temporal approach provides a better stabilization of the refraction with a significantly less SIA than superior approach. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5851 NEPJOPH 2012; 4(1): 54-58